Blunted hypoxic pulmonary vasoconstriction in apnoea divers. Issue 11 (16th September 2022) - Kelly, Tyler; Brown, Courtney; Bryant‐Ekstrand, Mohini; Lord, Rachel; Dawkins, Tony; Drane, Aimee; Futral, Joel E.; Barak, Otto; Dragun, Tanja; Stembridge, Michael; Spajić, Boris; Drviš, Ivan; et al.
Abstract : New Findings: What is the central question of this study? Does the hyperbaric, hypercapnic, acidotic, hypoxic stress of apnoea diving lead to greater pulmonary vasoreactivity and increased right heart work in apnoea divers? What is the main finding and its importance? Compared with sex‐ and age‐matched control subjects, divers experienced significantly less change in total pulmonary resistance in response to short‐duration isocapnic hypoxia. With oral sildenafil (50 mg), there were no differences in total pulmonary resistance between groups, suggesting that divers can maintain normal pulmonary artery tone in hypoxic conditions. Blunted hypoxic pulmonary vasoconstriction might be beneficial during apnoea diving. Abstract: Competitive apnoea divers dive repetitively to depths >50 m. During the final portions of ascent, divers experience significant hypoxaemia. Additionally, hyperbaria during diving increases thoracic blood volume while simultaneously reducing lung volume and increasing pulmonary artery pressure. We hypothesized that divers would have exaggerated hypoxic pulmonary vasoconstriction, leading to increased right heart work owing to their repetitive hypoxaemia and hyperbaria, and that the administration of sildenafil would have a greater effect in reducing pulmonary resistance in divers. We recruited 16 divers (Divers) and 16 age‐ and sex‐matched non‐diving control subjects (Controls). Using a double‐blinded, placebo‐controlled, cross‐over design, participants were evaluated for normal cardiac and lung function, then their cardiopulmonary responses to 20–30 min of isocapnic hypoxia (end‐tidal partial pressure of O2 = 50 mmHg) were measured 1 h after ingestion of 50 mg sildenafil or placebo. Cardiac structure and cardiopulmonary function were similar at baseline. With placebo, Divers had a significantly smaller increase in total pulmonary resistance than Controls after 20–30 min isocapnic hypoxia (change −3.85 ± 72.85 vs. 73.74 ± 91.06 dyns cm −5, P = 0.0222). With sildenafil, Divers and Controls had similar blunted increases in total pulmonary resistance after 20–30 min of hypoxia. Divers also had a significantly lower systemic vascular resistance after sildenafil in normoxia. These data indicate that repetitive apnoea diving leads to a blunted hypoxic pulmonary vasoconstriction. We suggest that this is a beneficial adaption allowing for increased cardiac output with reduced right heart work and thus reducing cardiac oxygen utilization in hypoxaemic conditions.